Analytical development and application of a targeted liquid chromatography-tandem mass spectrometry assay for chimeric aducanumab - Emma H. Doud; Kasi Hansen; Kathryn A. Haynes; Kierra Eldridge; Jaison Arrivalagan; Nitin Charbe; Lais Da Silva; Sara K. Quinney; Amber L. Mosley; Stacey J. Sukoff Rizzo; Paul R. Territo (mAbs)
A sensitive and specific liquid chromatography-tandem mass spectrometry assay was developed for the quantification of chimeric aducanumab (chAdu), a therapeutic antibody targeting pathological amyloid plaques in Alzheimer’s disease, in murine biological matrices. This method addresses the challenges of quantifying biotherapeutics in multiple tissue types within preclinical animal models with complex genetic backgrounds, where traditional enzyme-linked immunosorbent assay (ELISA) methods may suffer from interference and limited sensitivity. The assay uses parallel reaction monitoring on a Lumos Tribrid Orbitrap mass spectrometer, coupled with an Evosep LC system, and AssayMap Bravo-based automated sample processing. Key features include protein A enrichment for improved sensitivity, optimized peptide selection based on sequence uniqueness and ionization response, and incorporation of stable isotope-labeled peptides for accurate quantification. Assay performance was evaluated for selectivity, repeatability, and stability. The fit-for-purpose assay was successfully applied to quantify chAdu in both mouse cortex and plasma samples obtained from a pilot pharmacokinetic study of a mouse model of amyloid plaque deposition. This targeted mass spectrometry workflow offers a robust and reproducible alternative to ELISA for preclinical biotherapeutic analysis, particularly when dealing with complex biological samples.